2022
DOI: 10.1177/23259671221101875
|View full text |Cite
|
Sign up to set email alerts
|

Mid- to Long-Term Outcomes After Medial Open-Wedge High Tibial Osteotomy in Patients With Radiological Kissing Lesion

Abstract: Background: Although medial open-wedge high tibial osteotomy (MOWHTO) is the treatment of choice for patients with mild to moderate osteoarthritis with varus malalignment, concerns about inferior outcomes in patients with preoperative radiological kissing lesion (RKL) remain. Purpose: To compare the mid- to long-term clinical and radiological results and survivorship after MOWHTO in patients with versus without preoperative RKL. Study Design: Cohort study; Level of evidence, 3. Methods: Included were 122 knees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
0
7
0
2
Order By: Relevance
“…The main goal of a HTO is to improve patient function and relieve pain [ 8 ]. Undoubtedly, HTO has been revealed to enhance postoperative outcomes in patients with medial compartment osteoarthritis with varus deformity [ 38 ]. Numerous investigations aiming to identify the factors that contribute to favorable patient-reported outcomes following HTO have been actively pursued [ 6 , 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main goal of a HTO is to improve patient function and relieve pain [ 8 ]. Undoubtedly, HTO has been revealed to enhance postoperative outcomes in patients with medial compartment osteoarthritis with varus deformity [ 38 ]. Numerous investigations aiming to identify the factors that contribute to favorable patient-reported outcomes following HTO have been actively pursued [ 6 , 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that over-corrected surgery (weight-bearing line raito > 67%) was correlated with inferior patients’ reported outcomes. Traditionally, younger age is known to be associated with successful outcomes after HTO [ 38 ]. On the other hand, an opposite opinion was suggested.…”
Section: Discussionmentioning
confidence: 99%
“…[22] Birçok çalışma, PTVO ile birlikte kıkırdak tamir (subkondral drilleme, abrazyon artroplastisi, mikrokırık, kondrosit veya kök hücre implantasyonu) veya rekonstrüksiyon (allogreft transferi) yöntemleriyle birlikte uygulanmasını tavsiye etmiş, ameliyat sonrası 0-3° valgus açılanması olan hastalarda klinik sonuçların daha başarılı olduğunu bildirmiştir. [23][24][25][26] Kıkırdak hasarı ve varus dizilim bozukluğu olan hastalarda PTVO, tek başına veya aynı seansta kıkırdak tamir veya rekonstrüksiyon tedavileri ile birlikte de uygulanabilmektedir (Şekil 3). Hsu ve ark.…”
Section: (A) (B)unclassified
“…Hastaların beş yıllık takiplerinde hem klinik hem de ikincil bakı artroskopisinde kıkırdak hasarlarında belirgin iyileşme olduğunu tespit etmişlerdir. [26] Bode ve ark. çalışmalarında ortalama 4,9° varus deformitesi ve tam kat kıkırdak lezyonu olan 40 hastaya otolog kondrosit implantasyonu ile birlikte PTVO uygulamışlardır.…”
Section: (A) (B)unclassified
“…Medial opening wedge high tibial osteotomy (MOWHTO) is a well‐established surgical procedure for the treatment of medial compartment knee osteoarthritis (KOA) combined with varus deformity 12 . Much research 13–15 has shown that MOWHTO can effectively relieve pain and improve quality of life in patients with medial KOA, and avoid or delay knee replacement in these patients. Extensive soft tissue release and exposed osteotomy surface in MOWHTO can result in substantial perioperative bleeding, mean total blood loss ranged from 635.0 to 882.7 mL 16–19 …”
Section: Introductionmentioning
confidence: 99%